Moon, cosmic giant! The Moon is closest to Earth (perigee) and the Sun is furthest away (aphelion from Earth) - Dias, Luiz Ravell Andre Antonio; Tolentino, Ricardo José Vaz (Cadernos de Astronomia, 2024)
The article explores the relationship between the Sun and the Moon, despite their differing distances and sizes. It emphasizes the elliptical orbits causing variations in their apparent sizes, leading to events like eclipses. In July 2023, there was a coincidence of Earth being farther from the Sun and the Moon being closer, resulting in a larger apparent lunar size. The study highlights physical and orbital characteristics to comprehend such astronomical phenomena.